Lifeskill-Based Curriculum Development at Didaktika Uswatun Khasanah Kindergarten - Rohyati Rohyati; Fauzi fauzi (Edumaspul: Jurnal Pendidikan, 2023)
Life skills education must be taught from an early age, not only as a provision for children to live their daily lives but also to face future life challenges. This study aims to determine the process of implementing a life skills-based curriculum and to find out how the development of aspects in children with the application of a life skills-based curriculum at Didaktika Uswatun Khasanah Kindergarten. The research was conducted from January 1 to February 1, 2023, at Didaktika Uswatun Khasanah Kindergarten, Beji Village, Kedungbanteng District, Banyumas Regency. The research method used is descriptive qualitative, with data collection techniques using observation, interviews, and documentation techniques. The life skill-based curriculum implemented at Didaktika Uswatun Khasanah Kindergarten aims to prepare students who have an attitude of independence and hone plural intelligence and responsibility by the stage of child development so that children can master basic skills at the age stage of the child. The success of this life skills-based curriculum results from cooperation between students, teachers, and school community members and mutual support in implementing learning programs.